A case report of gastric linitis plastica diagnosed by endoscopic ultrasound-guided fine needle aspiration. Issue 50 (December 2017) - Muraoka, Shinji; Tsuchida, Kouhei; Iwasaki, Mari; Izawa, Naoya; Jinnai, Hidehito; Komatsubara, Toshinori; Tsunemi, Misako; Sakuma, Fumi; Kashima, Ken; Fukushi, Ko; Hiraishi, Hideyuki
Abstract: Rationale: There is currently no consensus on the ideal method for obtaining deep tissue biopsy material of advanced gastric LP. EUS-FNA has potential as a useful diagnostic method. Thus, we report the case of a 46-year-old male with advanced gastric linitis plastica (LP) who was diagnosed using endoscopic ultrasound-guided fine needle aspiration (EUS-FNA). Patient concerns: The patient underwent esophagogastroduodenoscopy (EGD) because of epigastric pain at a local clinic. The gastric fold swelling was pointed out by the EGD and despite the suspected advanced gastric LP, biopsy indicated Group 1. Repeat biopsy did not suggest malignancy. The patient was referred to our institution. Diagnoses: Endoscopic ultrasound indicated gastric wall thickening mainly in the greater curvature of the gastric corpus. Low-level echoes were detected throughout the entire gastric wall, and gastric wall layers had been disappeared. EUS-FNA of the gastric wall indicated signet ring cell carcinoma. Interventions: As a result of EUS - FNA, it became a policy to administer chemotherapy. In accordance with the patient's wishes, he was referred to another institution for chemotherapy. Outcomes: Normal biopsy did not give a definitive pathological diagnosis, and final diagnosis of LP was obtained with EUS-FNA. Lessons: We expect that EUS-FNA can be utilized as a relatively non-invasive, highly sensitive, and specific pathological diagnostic procedure for advanced gastric LP. EUS-FNA should be considered as one way to obtain a deep tissue biopsy of advanced gastric LP.